Untargeted plasma metabolomic fingerprinting highlights several biomarkers for the diagnosis and prognosis of coronavirus disease 19 - Occelli, Céline; Guigonis, Jean-Marie; Lindenthal, Sabine; Cagnard, Alexandre; Graslin, Fanny; Brglez, Vesna; Seitz-Polski, Barbara; Dellamonica, Jean; Levraut, Jacques; Pourcher, Thierry (Frontiers in Medicine, 2022)
Objectives: The COVID-19 pandemic has been a serious worldwide public health crisis since 2020 and is still challenging healthcare systems. New tools for the prognosis and diagnosis of COVID-19 patients remain important issues. Design: Here, we studied the metabolome of plasma samples of COVID-19 patients for the identification of prognosis biomarkers. Patients: Plasma samples of eighty-six SARS-CoV-2-infected subjects and twenty-four healthy controls were collected during the first peak of the COVID-19 pandemic in France in 2020. Main results: Plasma metabolome fingerprinting allowed the successful discrimination of healthy controls, mild SARS-CoV-2 subjects, and moderate and severe COVID-19 patients at hospital admission. We found a strong effect of SARS-CoV-2 infection on the plasma metabolome in mild cases. Our results revealed that plasma lipids and alterations in their saturation level are important biomarkers for the detection of the infection. We also identified deoxy-fructosyl-amino acids as new putative plasma biomarkers for SARS-CoV-2 infection and COVID-19 severity. Finally, our results highlight a key role for plasma levels of tryptophan and kynurenine in the symptoms of COVID-19 patients. Conclusions: Our results showed that plasma metabolome profiling is an efficient tool for the diagnosis and prognosis of SARS-CoV-2 infection.